2017
DOI: 10.4184/asj.2017.11.3.419
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Workplace Intervention for Chronic Low Back Pain among Nursing Assistants in Iran

Abstract: Study DesignInterventional research with a 6-month follow-up period.PurposeWe aimed to establish the effectiveness of a multidisciplinary workplace intervention on reduction of work-related low back pain (WRLBP), using ergonomic posture training coupled with an educational program based on social cognitive theory.Overview of LiteratureWRLBP is a major occupational problem among healthcare workers, who are often required to lift heavy loads. Patient handling is a particular requirement of nurse aides, and has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
(28 reference statements)
5
23
0
3
Order By: Relevance
“…Multifaceted Ergonomics 13 studies reporting on 15 different interventions were identified and grouped within the ergonomics domain [44][45][46][47][48][49][50][51][52][53][54][55][56]. 5 interventions from high-quality studies and 5 interventions from medium quality studies presented no effect of workplace ergonomics on MSD.…”
mentioning
confidence: 99%
“…Multifaceted Ergonomics 13 studies reporting on 15 different interventions were identified and grouped within the ergonomics domain [44][45][46][47][48][49][50][51][52][53][54][55][56]. 5 interventions from high-quality studies and 5 interventions from medium quality studies presented no effect of workplace ergonomics on MSD.…”
mentioning
confidence: 99%
“…Additionally, it is believed that certain patient handling maneuvers are more stressful, with higher injury risk, implying that they could have enormous improvement potential . These findings were supported in a study by Shojaei and colleagues (2017), which showed that a multidisciplinary workplace intervention employing social cognitive theory and using ergonomic posture training and education was effective in reducing the risk of work-related low back pain among nursing staff (Shojaei, Tavafian, Jamshidi, & Wagner, 2017). Garg and Kapellusch (2012) found out that implementation of ergonomics programs that involved modern patient-handling devices in seven nursing facilities resulted in a reduced number of injuries, workers' compensation costs, modified-duty days, and lost workdays linked to patient-handling tasks, despite an increase in the level of patient acuity post-intervention.…”
Section: Training Programs and Lifting Equipmentmentioning
confidence: 55%
“…However, during the study period, the rate of severe LBP among care workers at the intervention facility did not increase, while it doubled among the care workers at the non-intervention facility. Previous studies have reported that the rates of care workers’ LBP decreased after proper utilization of welfare equipment 1 , 2 , 3 , 4 , 5 , 6 ) , and after conducting education programs appropriate care methods and working posture 11 , 12 , 13 , 14 ) .…”
Section: Discussionmentioning
confidence: 99%